Cross-Sensory Correspondences: Heaviness is Dark and Low-Pitched. (July 2017) - Walker, Peter; Scallon, Gabrielle; Francis, Brian
Everyday language reveals how stimuli encoded in one sensory feature domain can possess qualities normally associated with a different domain (e.g., higher pitch sounds are bright, light in weight, sharp, and thin ). Such cross-sensory associations appear to reflect crosstalk among aligned (corresponding) feature dimensions, including brightness, heaviness, and sharpness. Evidence for heaviness being one such dimension is very limited, with heaviness appearing primarily as a verbal associate of other feature contrasts (e.g., darker objects and lower pitch sounds are heavier than their opposites). Given the presumed bidirectionality of the crosstalk between corresponding dimensions, heaviness should itself induce the cross-sensory associations observed elsewhere, including with brightness and pitch. Taking care to dissociate effects arising from the size and mass of an object, this is confirmed. When hidden objects varying independently in size and mass are lifted, objects that feel heavier are judged to be darker and to make lower pitch sounds than objects feeling less heavy. These judgements track the changes in perceived heaviness induced by the size-weight illusion. The potential involvement of language, natural scene statistics, and Bayesian processes in correspondences, and the effects they induce, is considered.